2001
DOI: 10.1093/oxfordjournals.rpd.a006506
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure to Patients During Paediatric Cardiac Catheterisation

Abstract: Radiation doses were investigated for 18 infants and children undergoing cardiac catheterisation procedures with thermoluminescence dosemeters. The range of integrated current values used during cardiac catheterisation procedure was wide, from 12.2 to 1195.8 mA.min (mean 604.9). The average was 22.9 mA.min for fluoroscopy, and 616.1 mA.min for cineangiography, and the ratio of cineangiography to fluoroscopy ranged from 10.5 to 89.5 with an average of 34.0. The cineangiographic contribution was estimated to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…(35) and from phantom testing of a similar C-arm CT system for neurovascular interventions (36). It is also well within the total estimated exposure during a routine pediatric cardiac catheterization (37)(38)(39)(40)(41). Finally, our measured exposure from ACT is significantly lower than the median exposure of 12 mSv for adult cardiac CT angiography in clinical use across 50 study sites recently reported by Hausleiter et al (42).…”
Section: Discussionsupporting
confidence: 78%
“…(35) and from phantom testing of a similar C-arm CT system for neurovascular interventions (36). It is also well within the total estimated exposure during a routine pediatric cardiac catheterization (37)(38)(39)(40)(41). Finally, our measured exposure from ACT is significantly lower than the median exposure of 12 mSv for adult cardiac CT angiography in clinical use across 50 study sites recently reported by Hausleiter et al (42).…”
Section: Discussionsupporting
confidence: 78%
“…However, patient exposures to x-rays used in these complicated procedures can be high. 2,9 Furthermore, x-ray doses in pediatric cardiac catheterizations are especially critical in view of the enhanced radiosensitivity of children compared with adults. 3,7 One should also take into account that in children with congenital heart disease, there is often a need to perform multiple examinations, resulting in an increase in the radiation risk.…”
Section: Discussionmentioning
confidence: 99%
“…14 Only one study reported a mean entrance skin dose of 481 mGy for children Ͻ10 years of age. 15 Because of the moderate values of skin doses in pediatric catheterizations, radiation-induced skin injuries are unlikely. On the other hand, skin dose has to be monitored so that the cardiologist knows the maximum skin dose delivered during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…12 Most of the radiation dosimetry studies performed in pediatric patients are based on measurements with thermoluminescence dosimeters (TLDs) for estimating the dose to the skin, thyroid, and gonads. [12][13][14][15][16] Other studies have indicated the dose-area product (DAP). 10,12,17,18,21 However, to assess the potential risk for stochastic effects such as cancer and leukemia resulting from cardiac catheterization procedures, the effective dose should be calculated.…”
mentioning
confidence: 99%